HYDROTREATING OF KEROSENE FRACTIONS IN THE PRODUCTION OF JET FUELS - Efymenko, Valery V.; Kuzmenko, Tetyana O. (Proceedings of National Aviation University (archive), 2009)
The features of hydrotreating processing of kerosene fractions are considered .Usage of more effective catalyst for the production of high-quality jet fuel is offered.